(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2026)
The cleaning efficiency of cotton of grades I and III in the MQZH-15 type cleaner for cleaning cotton from small impurities was 10.5 (abs)% and 9.6 (abs)% lower than the cleaning efficiency in the technical specifications, depending on the grade, and showed that it could not meet the technological requirements.